2023
DOI: 10.1099/jmm.0.001768
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses of Bacteroides fragilis: subdivisions I and II represent distinct species

Jamie English,
Fiona Newberry,
Lesley Hoyles
et al.

Abstract: Introduction. Bacteroides fragilis is a Gram-negative anaerobe that is a member of the human gastrointestinal microbiota and is frequently found as an extra-intestinal opportunistic pathogen. B. fragilis comprises two distinct groups – divisions I and II – characterized by the presence/absence of genes [cepA and ccrA (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 122 publications
(222 reference statements)
1
2
0
Order By: Relevance
“…Based on the phylogeny of the core genome alignment by maximum likelihood, midpoint-rooted, divisions I and II also separate into discrete clades (Figure 1F) . Collectively, these analyses reinforce the recent proposal to classify B. fragilis division II strains as a novel species (Wallace et al, 2022; English et al, 2023).…”
Section: Observationsupporting
confidence: 84%
See 2 more Smart Citations
“…Based on the phylogeny of the core genome alignment by maximum likelihood, midpoint-rooted, divisions I and II also separate into discrete clades (Figure 1F) . Collectively, these analyses reinforce the recent proposal to classify B. fragilis division II strains as a novel species (Wallace et al, 2022; English et al, 2023).…”
Section: Observationsupporting
confidence: 84%
“…Bacteroides fragilis is a persistent colonizer of the human gut and has been linked to both health and disease (Wexler, 2007). Multiple studies have reported two distinct, monophyletic groups within B. fragilis , referred to as division I and division II, which share 87% average nucleotide identity, while the typical species cutoff is 96% (Johnson, 1978; Podglajen et al, 1995; Ruimy et al, 1996; Gutacker et al, 2000; Nagy et al, 2011; Wallace et al, 2022; English et al, 2023). Here, we use comparative genomics to identify the genetic differences between division I and II strains, to provide further evidence for the classification of these divisions as two distinct species (Wallace et al, 2022; English et al, 2023).…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…They have primarily been differentiated through the presence of cepA , a beta-lactamase, which is unique to division I ( 2 ), and the chromosomally encoded carbapenemase gene ( cfiA or ccrA ), which is unique to division II and provides resistance to beta-lactamase inhibitors ( 3 , 4 ). Due to their genetic similarity, traditional methods such as 16S rRNA gene analysis cannot distinguish between these divisions, yet they share an average nucleotide identity (ANI) of 87%, below the typical species cutoff of 96% ( 3 , 5 10 ). Here, we conduct a comprehensive genomic comparison and identified genes conserved within each B. fragilis division, but not shared between them, shedding light on the unique biological roles and functions of these divisions within their ecological niches.…”
Section: Observationmentioning
confidence: 99%